Kewenangan Mahkamah Konstitusi dalam Menguji Peraturan Pemerintah Pengganti Undang-Undang - Riri Nazriyah (Fakultas Hukum Universitas Islam Indonesia, 2010)
This research is focused on the competency of Constitutional Court to review Perpu. The analyzed problem is judicial review by Constitutional Court over Perpu. This research is a normative research. The characteristic of this research is prescriptive research, which is a research purposed to obtain suggestions on how to solve the problem. The research approach applied in this research includes statute approach and case approach. The data used in the research is secondary data. The result of this research is that Constitutional Court has competency to perform judicial review over Perpu, although Constitution does not clearly grant authority to Constitutional Court. Consideration used by Constitutional Court judges to review Perpu is teleological and sociological factor due to developing society needs.Key words : Competency, examination, vacuum of law